2019
DOI: 10.1128/mbio.02895-18
|View full text |Cite
|
Sign up to set email alerts
|

Dual β-Lactam Combinations Highly Active against Mycobacterium abscessus Complex In Vitro

Abstract: The emergence of chronic MABC infections among immunocompromised populations and their inherent and acquired resistance to effective antibiotic therapy have created clinical challenges in advancing patients for transplant surgery and treating those with disease. There is an urgent need for new treatment regimens, and the repurposing of existing antibiotics provides a rapid strategy to advance a laboratory finding to patient care. Our recent discoveries that dual β-lactams, specifically the combination of cefta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 43 publications
0
58
1
Order By: Relevance
“…One strategy that would allow for rapid implementation of effective treatments in the clinical setting involves repurposing of commercially available antibiotics in novel combinations. Several studies have demonstrated in vitro synergy between various antibiotics against M. abscessus, which, when used in combination, have the potential to overcome drug resistance (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…One strategy that would allow for rapid implementation of effective treatments in the clinical setting involves repurposing of commercially available antibiotics in novel combinations. Several studies have demonstrated in vitro synergy between various antibiotics against M. abscessus, which, when used in combination, have the potential to overcome drug resistance (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Zidebactam had a more modest effect on cefepime MICs and cefepime has lower intrinsic activity against MABC than meropenem. However, emerging evidence suggests that combinations of two β-lactams with an effective BLI could be synergistic against M. abscessus (12, 23, 24). Our study identified β-lactams belonging to several sub-classes that are potentiated by new BLIs and could be combined with a fixed β-lactam/BLI combination to pursue such synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the outstanding contribution of β-lactam antibiotics to treatment of infectious diseases, their utility against MABC organisms is limited by a chromosomally encoded, broad-spectrum, Ambler class A β-lactamase, BlaMab, which is the major determinant of intrinsic β-lactam resistance in MABC (6). While older β-lactam-based β-lactamase inhibitors (BLIs) such as clavulanate, tazobactam and sulbactam are ineffective against BlaMab and do not improve the in vitro activity of β-lactam antibiotics against MABC organisms (7, 8), we and others have shown that the new diazabicyclooctane-based BLIs avibactam and relebactam, developed to treat multidrug-resistant Gram-negative bacteria (9), do improve the in vitro activity of many β-lactam antibiotics against MABC organisms, particularly carbapenems and cephalosporins (8, 1012). Avibactam and relebactam have been developed with ceftazidime and imipenem, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study demonstrated the inhibitory activity of avibactam, a non- β -lactam β -lactamase inhibitor, against Bla Mab significantly improving the in vitro and in vivo activity of imipenem (Lefebvre et al 2016). Very recently, a number of studies have been published demonstrating a number of β -lactam combinations displaying high levels of in vitro synergistic activity against M. abscessus complex (Pandey et al 2019) (Story-Roller et al 2019). Furthermore, a recent study identified the in vitro activity of two new non- β -lactam β -lactamase inhibitors, namely relebactam and vaborbactam, demonstrating synergistic activity between imipenem and relebactam as well as meropenem and vaborbactam (Kaushik et al 2019).…”
Section: Introductionmentioning
confidence: 99%